The integrated academic information system support for education 3.0 in higher education institution: lecturer perspective - Utomo, Hadi Prasetyo; Bon, Abdul Talib; Hendayun, Mokhamad (IOP Publishing, 2018)
Education 3.0 has been implemented in many higher education institutions (HEIs). Education 3.0 has been directed the institution toward better educational experience. But on the other hands, the implementation of Education 3.0 also caused some problems. Previous research has found administrative problem experienced by the lecturer. This research explores deeper from the lecturer and suggested the solution from lecturer perspective, combined with information technology capabilities owned by the HEIs. The research used a case study as the method and conducted a qualitative research with a semi-structured interview. The interview analysis has found that the increase of the administrative processes is caused by online and offline administrative activities. The online activities are from e-learning and the offline activities are from traditional learning (face-to-face). The administrative processes also involved the academic information system (AIS). Simplified all of the administrative processes are more preferred. To overcome the problems, integrating the AIS and e-learning become necessary. This research suggests transforming the existing AIS into an integrated AIS and hopes the solution can simplify the administration process.